Ecological Study of Rare-Actinomycetes in Soils and Leaf-Litters - Lisdiyanti, Puspita; Ratnakomala, Shanti; Ridwan, Roni; Widyastuti, Yantyati; Otoguro, Misa; Ando, Katsuhiko (Annales Bogorienses, 2011)
A total of 268 strains of Actinomycetes were isolated from soil and leaf-litter samples collected in Jambi (Sumatera) and Cibinong (West Java) using three selective isolation methods. All the isolates were identified by morphological characteristic and by analysis of 16S rDNA sequence. On the basis of their morphology and 16S rDNA sequence, 164 isolates were belonged to the Streptomyces Group and 104 isolates were belonged to the Rare-Actinomycetes (Non-Streptomyces) Group. Furthermore, 40% of isolates in Streptomyces Group and 62% of isolates in Non-Streptomyces Group are supposed to be new taxa. It is indicated the richness of Actinomycetes in these two area. The genus Streptomyces is the most abundant in soil samples, occupying 60-75% of all isolates; while the genus Actinoplanes is mainly found in leaf-litter samples (70%). The use of selective isolation media is important to elucidate the microbial diversity.